Stimuli Behind SMEs' Export Decisions: Evidence From an Emerging Country During the COVID-19 Pandemic - Mercan, Murat Anil; Keskin, Halit; Kalaycioglu, Ozan; Basar, Dogan (WILEY, 2025)
Executive Summary: In this study, we focus on small and medium enterprise management's motivations for exporting and the effects of the coronavirus disease-19 (COVID-19) pandemic on exports. Turkish firms registered as exporter companies in official export unions as of March 2022 were surveyed. A total of 17 questions were included in the survey: seven questions on proactive reasons, six questions on reactive reasons, and four questions regarding the pandemic. One-way ANOVA was used for analyses. The results suggest that tax benefits are among the most important determinants of exporting for larger companies. Another important reason, according to managers, is that firms can achieve economies of scale through exporting. Additionally, our findings suggest that even if firms seek to take advantage of export opportunities created by the pandemic, exporting does not happen as expected. Our study makes several important contributions to the literature because it is the first to measure the effects of COVID-19 on exporting from the perspective of managers. Additionally, we investigate the management's motivations for exporting using microdata from T & uuml;rkiye. Managerial Implications of the Study: This study shows the importance of the determinants of exports from a managerial perspective. Therefore, our study will be of great help to managers when they decide to start exporting. It also provides them with an opportunity to understand what other managers consider important in exports. Originality/Value: This study provides information about the effects of the COVID-19 pandemic on exporting from managers' perspectives and investigates management's motivations for exporting using microdata from T & uuml;rkiye, which has not been previously studied.
Keywords: export decision; export stimuli; exporting SMEs; MEDIUM ENTERPRISES; CONTINGENCY THEORY; SMALL FIRMS; PERFORMANCE; INTERNATIONALIZATION; STRATEGY; RESOURCES; CRISIS; IMPACT; ORGANIZATION; Business & Economics